Overlapping of mental health symptoms and post-concussion symptoms among Icelandic female athletes - Arna Ýr Arnardóttir 1983- (2020)
Studies on the relationship between sports-related concussion (SRC) and mental health symptoms have in the past been mainly focusing on male athletes. Non-specific post-concussion symptoms (PCS) can also be found in a healthy population. It is therefore important to analyze PCS that are overlapping with mental health symptoms. This study examined overlapping of two mental health questionnaires, depression (PHQ-9) and anxiety (GAD-7), with self-report symptoms on the post-concussion symptoms scale (PCSS), among elite female athletes in Iceland. The aim was to examine the correlation between those items that were found to be overlapping with concussion count of two to six or more SRC. Concussion count with individual items on PHQ-9 and GAD-7 was also tested. The hypothesis tested in the study was, that there is overlapping of PHQ-9, GAD-7 and PCSS symptoms and there is a strong relationship between overlapping symptoms among female athletes with two to six or more SRC.The final sample was (N = 452), 18-45 years (M = 26.99). Rannsóknir sem hafa verið gerðar á sambandinu milli heilahristings hjá íþróttafólki og andlegra einkenna hafa flestar einblínt á karlkyns íþróttafólk, því hafa konur ekki verið rannsakaðar eins mikið. Heilahristingseinkenni sem geta komið fram í kjölfar heilhristings eru ekki endilega sértæk fyrir heilahristing. Sömu einkenni geta líka verið greind af öðrum ástæðum hjá einstaklingi sem hefur ekki fengið heilahristing. Það er því mikilvægt að greina samslátt þessara einkenna sem skarast í einkennapör og að skoða þessi pör sérstaklega. Rannsókn þessi skoðar einkennasamslátt á milli 22 atriða heilahristing einkennaskalans (PCSS) og tveggja sálfræðilegra mælitækja sem meta þunglyndi (PHQ-9) og kvíða (GAD-7) hjá íslenskum íþróttakonum. Markmið rannsóknarinnar var að skoða fylgni á milli þeirra einkenna sem metin voru hafa skarast hjá þeim konum sem höfðu fengið tvo til sex eða fleiri heilahristinga. Þátttakendur í lokaúrtakinu voru (N=452), á aldrinum 18-45 ára (M=26.99). Niðurstöður sýndu að ...